SCAFFOLDING STRATEGY FOR THE LOW-MOTIVATED STUDENTS IN WRITING - Ningrum, Ary Setya Budhi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
Writing is one of the basic language skills that should be mastered by English department students. By mastering this skill, they are expected to be able to express their feelings, thoughts, and ideas in written form. However, most of the students said that writing is difficult subject, and they always face some problems in writing. The most serious problems arise when the students have negative attitude about writing or lack confidence in themselves as writers. To overcome the problem, scaffolding strategy in the process of writing is an alternative strategy to improve the low-motivated students? ability in writing.